Disentangling food security from subsistence agriculture in Malawi - Benson, Todd (International Food Policy Research Institute, 2021)
Malawi’s many smallholders rely heavily on rainfed, low-input subsistence farming to meet their food needs. Yet for most rural Malawian households, subsistence agriculture cannot consistently produce enough food to ward off hunger. Nor can they rely on the country’s weak markets to buy additional food they may require or to profitably sell their agricultural products throughout the year. Government policies have long prioritized agricultural production among marginal farmers for food security rather than broader policies of economic diversification, market expansion, and growth. The book identifies crucial changes that could improve food security and, in the long term, facilitate agricultural transformation. Decades of research in Malawi are synthesized to propose policy solutions for the country’s persistent food insecurity and for agricultural transformation that could drive long-term economic growth. This work should be useful to policymakers, development specialists, and others concerned with how Malawi or other countries facing similar rural economic development challenges can realize sustainable food security.